HUBUNGAN JUMLAH PARITAS DAN IMT (INDEKS MASSA TUBUH) DENGAN GAMBARAN HISTOPATOLOGI KANKER OVARIUM DI RSPAD GATOT SOEBROTO TAHUN 2019 - 2020 - Muhammad Rizky Akbar, (2023)
Introduction: Ovarian cancer is one of the most common gynecological cancers in the world with a high mortality rate. Therefore, it is necessary to take preventive measures to prevent an increase in the incidence of cases. However, previous research still shows contradictory results. Purpose: This study aims to determine the relationship between parity numbers and body mass index (BMI) with histopathological features of ovarian cancer at Gatot Soebroto Army Hospital in 2019-2020. Method: This research is an observational analytic study with a cross-sectional design using secondary data in the form of medical records. The inclusion criteria for the study were patients diagnosed with ovarian cancer, ovarian cancer patients being treated at the Gatot Soebroto Army Hospital in the 2019-2020 period, and data in the form of height, body weight, number of parities, and histopathological type of ovarian cancer in the patient's medical record. Meanwhile, the exclusion criteria included incomplete medical record data and ovarian cancer patients who did not undergo surgery. Samples were selected using total population sampling. Data analysis was performed by determining the percentage for each category and Chi-square test to determine the relationship between variables. Result: Based on the results of the study, it was found that the majority of patients had type I epithelial ovarian cancer as many as 49 people (53.3%). According to the number of parities, BMI category, and histopathological type of ovarian cancer, the majority of patients at Gatot Soebroto Army Hospital were nullipara totaling 36 (39.1%), obese totaling 31 (33,7), and the most prevalent histopathological type was type I. epitheial totaling 49 (53.3%). Conclusion: Data analysis showed that there was no significant relationship between parity and BMI with the histopathological features of ovarian cancer. It is suggested for further researchers to develop this research in terms of variables, sample size, design, and research instruments.